Método de estudio de casos y comprensión lectora en los estudiantes del cuarto grado de primaria de la i.e. "virgen del carmen", Trujillo - 2014 - Príncipe Gonzáles, Edith Karla (2016)
The purpose of this research was to identify the influence of the case study method in reading comprehension of a group of students from the fourth grade of IEAC "Virgen del Carmen", the sector of the district Victor Raul "El Porvenir". Applied research is quasi-experimental with control group and experimental group pre-test and post-test. The sample consisted of 56 students, divided into two groups. Fourth grade "A" as experimental group and the fourth grade "B" as the control group, each with 28 students. The independent variable was the case study method and was applied through a twelve sessions held for three months with one session per week and lasts forty-five minutes and the dependent variable measure reading comprehension pretest and posttest. After the implementation of the program the students in the experimental group improved by 32.85% significance.